Korelasi Kepemimpinan Transformasional Dengan Kepuasan Kerja Dosen di Bandung - Moh. Sulhan; Nandang Abdurohim; Muhammad Hafiz (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
This study uses quantitative methods, data analysis consists of instrument test (validity and reliability), partial indicator analysis test, prerequisite test (normality and linearity) correlation test (coefficient and coefficient of determination). The results of this study can be concluded that: (a) Transformational Leadership is included in the sufficient category, because it is in the range of 2.60 – 3.39 with an average value of 3.38 (enough category); (b) Lecturer job satisfaction is included in the sufficient category, because the range is based on 2.60 – 3.39 with an average value of 3.33 (enough category); (c) The relationship between transformational leadership and job satisfaction of lecturers has a relationship from the calculation results of the correlation coefficient analysis obtained is 0.881. There is a very strong level because it is in the 0.80 – 1,000 category which means that there is a very strong relationship.